Kepribadian proaktif dan job hopping intention: Menguji kepuasan kerja sebagai mediator: Proactive personality and job hopping intention: Testing job satisfaction as a mediator - Tifania Krisma Rahardyana; Pratista Arya Satwika (Persona:Jurnal Psikologi Indonesia, 2025)
The phenomenon of employees who tend to change jobs is increasingly widespread, especially among Generation Z, who tend to leave their jobs in less than six months, which makes it challenging for organizations to retain their employees. This study aims to examine the relationship between proactive personality and job-hopping intention, as well as the mediating role of job satisfaction in this relationship. The instruments used in this study were the Job-Hopping Intention Scale (α=0.880), the Proactive Personality Scale (α=0.839), and the Job Satisfaction Survey (α=0.920). The research method used is quantitative, involving 114 respondents who are Generation Z employees in Jabodetabek and have less than two years of service.  Data were analyzed using the PROCESS Macro for SPSS (Model 4) developed by Hayes. The results showed that job satisfaction has a significant effect in mediating the relationship between proactive personality and job-hopping intention. Thus, job satisfaction is an important aspect in reducing employees’ job-hopping intention. Companies are expected to develop programs to increase employee job satisfaction, such as career coaching, reward systems, supportive work environments, and greater job autonomy.